Online social anxiety and mobile instant messaging adoption and continuance usage intention: How does it relate to social, technical, and mobility factors? - Charlie Chen; Shanshan Lou; Laddawan Kaewkitipong (Cogent Business & Management, 2022)
The rise in MIM apps usage have resulted in increased interruptions to people daily social life, causing distractions and online social anxiety. The purpose of this study is to investigate the influence of social, technical, and mobility factors on social anxiety, as well as the initial and continuation intention of users of MIM applications. We surveyed 231 Taiwanese users of the leading MIM app LINE. Smart-PLS was adopted to analyze social, technical, mobility, social anxiety, and MIM continuation intentions. Our findings show that online social anxiety can decrease both initial and continuation intentions for MIM apps. Moreover, online social anxiety moderates the relationship between initial and continuance adoption intentions. However, social, technical, and mobility factors appears to have positive influences on the initial MIM adoption intention. Therefore, the three factors can be integrated to promote MIM app use without increasing social anxiety.
Keywords: 650; adoption intention; communication control capacity; continuance usage intention; MIM applications; mobility; online social anxiety; perceived subjective norm